2018
DOI: 10.1007/s11524-018-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Incarceration and Transactional Sex among HIV-infected Young Men Who Have Sex with Men in the United States

Abstract: Criminal justice practices in the USA disproportionately affect sexual and racial/ethnic minority men, who are at higher risk of incarceration. Previous research demonstrates associations between incarceration and sexual risk behaviors for men who have sex with men (MSM). However, little of this work focuses on young MSM (YMSM), particularly HIV-infected YMSM, despite nearly one-third reporting engagement in sexual risk behaviors, such as transactional sex. We therefore explored the association between incarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In addition to recent CJ involvement, we found older AAMSM and those using drugs were also more likely to get involved in transactional sex. Similar findings have been observed in another study of HIV-infected young MSM where participants aged 24 or older were more likely to report history of transactional sex than those younger than 24, suggesting risk of engaging in transactional sex may have increased over life course, such as multiple incarcerations [14]. The association between transactional sex and substance use also has been well documented in previous studies [10,11,21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to recent CJ involvement, we found older AAMSM and those using drugs were also more likely to get involved in transactional sex. Similar findings have been observed in another study of HIV-infected young MSM where participants aged 24 or older were more likely to report history of transactional sex than those younger than 24, suggesting risk of engaging in transactional sex may have increased over life course, such as multiple incarcerations [14]. The association between transactional sex and substance use also has been well documented in previous studies [10,11,21].…”
Section: Discussionsupporting
confidence: 86%
“…The limited studies exploring the association between CJ involvement and transactional sex among MSM mainly focused on a lifetime experience. For example, one study of a sample of primarily racial/ethnic minority young HIV-positive MSM found that history of incarceration was independently associated with history of transactional sex [14]. The association between recent history of CJ involvement and transactional sex among AAMSM merits further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…While this may be considered comparable to another review reporting a pooled prevalence of 20.1% among HIV-infected adolescents in sSA [31], the combined estimates are much lower compared to the 20.6-60.0% range reported in another review involving HIV-infected adolescents aged 10-24 years from sSA [16]. Further, a study of HIV-infected adolescents and young men who have sex with men (MSM) from the USA reported a 27.8% prevalence of TS [32] which is higher than our estimate. The distinct difference in estimates reported in the three reviews from sSA and the US study may be a reflection of the complexities involved in the definition of TS in different African contexts [16] and may warrant development and validation of a standardized and context relevant approach in the definition of TS in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Research has yet to explore sexual orientation discrimination’s association with criminal justice involvement, but does show how factors related to sexual orientation might influence such involvement—particularly through pathways like community-level discrimination and social disadvantage including YMSM being kicked out of their homes and lack of employment opportunities. Sexual orientation discrimination and marginalization can lead to substance use (Hatzenbuehler et al, 2015) and survival sex which, in turn, are associated with criminal justice involvement (Philbin et al, 2018); sexual orientation discrimination can also limit social engagement in community organizations and peer groups which facilitates healthy adolescent development (Meyer, 2003).…”
Section: Discussionmentioning
confidence: 99%